2017
DOI: 10.3233/cbm-170577
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-513c suppresses neuroblastoma cell migration, invasion, and proliferation through direct targeting glutaminase (GLS)

Abstract: Neuroblastoma is a brain malignancy of childhood and accounts for 7-10% of childhood cancers, leading to approximately 15% of pediatric cancer deaths. MicroRNAs (miRNAs) are a family of short (about 18-25 nucleotides), noncoding and single stranded endogenous RNAs, which complementarily bind to the 3' untranslated regions of their target genes. Recently, glutamine metabolism has been recognized as an important nutrition source for tumor cells, and hence targeting glutamine metabolism could benefit to developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…The Streicher's group indicated that in cutaneous melanoma, the miR-506-514 cluster was consistently overexpressed and mediated the melanocytes transformation [37]. On the other hand, it has been shown that the downregulation of hsa-miR-513c promotes the proliferation and invasiveness of neuroblastoma and glioma cells [38,39]. Similar to that downregulation of hsa-miR-506, leads to increased proliferation, invasiveness, and epithelial to mesenchymal transition in breast gastric and ovarian cancer [40][41][42].…”
Section: Discussionmentioning
confidence: 97%
“…The Streicher's group indicated that in cutaneous melanoma, the miR-506-514 cluster was consistently overexpressed and mediated the melanocytes transformation [37]. On the other hand, it has been shown that the downregulation of hsa-miR-513c promotes the proliferation and invasiveness of neuroblastoma and glioma cells [38,39]. Similar to that downregulation of hsa-miR-506, leads to increased proliferation, invasiveness, and epithelial to mesenchymal transition in breast gastric and ovarian cancer [40][41][42].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, miR‐204 may also be involved in the chondrogenic differentiation of periodontal ligament stem cells . miR‐513c was reported to inhibit the development of nervous system tumours and hepatocellular carcinoma . Nevertheless, little research has been conducted to reveal their roles in periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…64 miR-513c was reported to inhibit the development of nervous system tumours and hepatocellular carcinoma. [65][66][67] Nevertheless, little research has been conducted to reveal their roles in periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was attributed to the decrease in GLS mRNA, since it is a direct target of miR-513c. These findings suggest that miR-513c may act as a tumor suppressor and deserves to be studied for consideration in neuroblastoma treatment [114] (Figure 2).…”
Section: Mir-513cmentioning
confidence: 97%